HUBUNGAN ASUPAN ENERGI DENGAN KEJADIAN OBESITAS PADA SISWA SEKOLAH DASAR DI KOTA MANADO - Yamin, Bahrudin; Mayulu, Nelly; Rottie, Julia (JURNAL KEPERAWATAN)
Abstract: Obesity is a pathological condition in the presence of excessive fat accumulation of what is required for the function of the body. Obesity in terms of health is one of the nutritional disease, as a result of consuming food that far exceeds their needs This study aims to determine the relationship of energy intake with the incidence of obesity among primary school students in the city of Manado with analytical survey method using a Case Control design (Case Control ) sample 136 using the chi-square test (x2), at the 95% significance level (α 0.05). research proves that there is a significant correlation between high energy intake with the incidence of obesity among primary school students in the city of Manado conclusion there is a significant association between energy intake with the incidence of obesity with p = 0.002. High energy intake of the obtained value Odds Ratio (OR) of 4.058 (95% CI = 1.320 to 2.417), suggestions should be made prevention through nutrition counseling about obesity and risk factors of obesity in primary school students in each school through school health promotion programs by the Department of Health and in collaboration with relevant agencies. Keywords: children, energy intake, obesity Abstrak: Obesitas merupakan keadaan patologis dengan terdapatnya penimbunan lemak yang berlebihan dari apa yang diperlukan untuk fungsi tubuh. Obesitas dari segi kesehatan merupakan salah satu penyakit gizi, sebagai akibat mengkomsumsi makanan yang jauh melebihi kebutuhannya Penelitian ini bertujuan mengetahui hubungan asupan energi dengan kejadian obesitas pada siswa sekolah dasar di kota Manado dengan metode penelitian survei analitik dengan menggunakan rancangan Case Control (kasus kontrol) sampel 136 menggunakan uji chi-square (x2), pada tingkat kemaknaan 95% (α 0,05).Hasil penelitian membuktikan bahwa terdapat hubungan yang bermakna antara asupan energi yang tinggi dengan kejadian obesitas pada siswa sekolah dasar di Kota Manado kesimpulan Terdapat hubungan yang bermakna antara asupan energi dengan kejadian obesitas dengan nilai p sebesar =0,002. Jumlah asupan energi yang tinggi maka diperoleh nilai Odds Ratio (OR) sebesar 4,058 (95% CI = 1,320-2,417), saran perlu dilakukan pencegahan melalui penyuluhan gizi tentang obesitas dan faktor-faktor resiko terjadinya obesitas pada siswa sekolah dasar di masing-masing sekolah melalui program peningkatan kesehatan sekolah oleh Dinas Kesehatan dan bekerja sama dengan instansi-instansi terkait Kata kunci : anak-anak, asupan energi, obesitas